Structural performance of concrete-filled cold-formed high-strength steel octagonal tubular stub columns. (15th July 2021) - Fang, Han; Chan, Tak-Ming; Young, Ben
Highlights: Behaviour of concrete-filled CFHSS octagonal tube stub columns was studied. Stub column tests and numerical modelling were performed for the study. The applicability of existing design approaches was assessed and discussed. A design approach was proposed to accurately estimate the structural strengths. Abstract: This paper presents a comprehensive experimental and numerical study on the structural performance of concrete-filled cold-formed high-strength steel octagonal tubular stub columns. Stub column specimens formed using high-strength steel and infilled concrete with grades C50 and C90, and with three different plate width-to-thickness ratios were tested. The ultimate loads, load-displacement responses and failure modes of the structures were observed and discussed. In addition to the experimental investigations, a finite element model validated using the stub column test results was developed. A series of parametric studies were subsequently conducted to obtain supplementary data for concrete-filled cold-formed high-strength steel octagonal tubular stub columns with a wide range of plate width-to-thickness ratios and different concrete compressive strengths. The applicability of existing design approaches in European and American standards and in literature provided for concrete-filled steel tubular structures with rectangular, circular or octagonal cross-sections were evaluated using the results obtained from the experimental and numerical study. The accuracy of design predictions for concrete-filled cold-formed high-strength steel octagonal tubular stub columns using different design approaches was discussed. A design approach that more accurately incorporates the strength contributions from steel tubes and concrete infill was also proposed for structural design.